Aseptic addition method for Lactobacillus casei assay of folate activity in human serum - Herbert, Victor (1966)
An `aseptic addition' method is described for microbiological assay with Lactobacillis casei of folate activity in human serum. It has the following advantages over the previously reported `standard' method. 1 The manipulations involved in the assay are halved, by deleting autoclaving of serum in buffers. 2 The use of 1 g.% ascorbate better preserves serum folates than the lower amounts of ascorbate which are the maximum quantities usable in the standard methods. 3 Only 0·3 ml. of serum is required (0·1 ml. for one sample; 0·2 ml. for its duplicate).